PROBLEMATIKA PERKAWINAN TIDAK TERCATAT (NIKAH SIRI) DAN SOLUSI HUKUMNYA - Mardani Mardani; Sardjana Orba Manullang; Yessy Kusumadewi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
This study aims to comprehensively describe the problems of unregistered marriages (sirri marriages) and their legal solutions. This study is a literature study that explains in detail the issues of unregistered marriages (sirri marriages) and their legal solutions. The data collection technique used in this research is the documentation technique. While the analysis technique used in this research is descriptive. After conducting in-depth research, an important conclusion was found that unregistered or unregistered marriages are events that still occur in society in the modern era as it is today. There are many factors that cause people not to register/register their marriage to the Office of Religious Affairs (KUA), including because they think that marriage is a personal matter so that the state does not need to interfere, they are worried that their pension money will be lost when registering their marriage, the marriage is carried out in minors, due to pregnancy out of wedlock. Unregistered marriages have negative impacts, including; The marriage does not have legal power and certainty, so it is difficult to claim his rights in the event of a divorce, and difficult in matters related to state administration, such as making a marriage certificate and others. Meanwhile, the positive impact is that a registered marriage can provide protection to the family and legal certainty. The role of the government to resolve cases of unregistered marriages is to carry out marriage istbat in an integrated and programmed manner for free.